Modification of Reinforced Concrete Retaining Wall at Pilangbango Reservoir Construction Project Madiun, East Java - Mudji Irmawan; Yerry Kahaditu Firmansyah; Afif Navir Refani (IPTEK Journal of Proceedings Series, 2017)
The reservoir is the tendon of water in order to accommodate the excess rain water in the rainy season and its utilization in the dry season for various purposes, both in the field of agriculture as well as the interests of the community. To find out the cause of the crack wall of the reservoir Pilangbango Madiun, East Java, then do the test strongly press on concrete walls and soil investigations on the area of the reservoir. Spunpile 400 mm in diameter used by the mounting distance 200 cm and a depth of 12 m and pole mounted on the heels of concrete walls. Manual calculation of the results and analysis of the Finite Element program it can be concluded that in the presence of an additional retaining her 400 spunpile mm using a distance 200 cm and a depth of 12 m, retaining wall construction is then quite able to hold style pillow case and Sliding with style has a safety factor more than 1.5. So the movement of the sliding walls do not happen again.